Irisin administration modifies ovary mast cell numbers, ovarian angiogenesis, and oxytocin levels in obese rats - Ertugrul, Nazife Ulker; Ertugrul, Tugrul; Yardimci, Ahmet; Tektemur, Nalan Kaya; Gokdere, Ebru; Delice, Nurcan; Canpolat, Sinan (Univ Zagreb Vet Faculty, 2024)
Exercise hormone irisin, a thermogenic adipo-myokine, promotes energy expenditure by white adipose tissue browning. Considering that irisin improves the white adipose tissue metabolic profile and increases whole-body energy expenditure, it is thought that irisin may be a potential new therapeutic target for the treatment of the growing epidemic of obesity. The roles of mast cells and angiogenesis in the pathogenesis of obesity are known, and the importance of loss of mast cell function and antiangiogenic agents in the treatment of obesity has gained prominence in recent years. In addition, the therapeutic efficacy of oxytocin for obesity, by inducing browning and stimulating thermogenesis, is also noteworthy. To understand better the mechanisms involved in the therapeutic effect of irisin on obesity, the present study evaluated the effects of irisin treatment on high-fat diet-induced, obese female rats, focusing on the number of ovary mast cells, and ovarian angiogenesis and serum oxytocin levels. Our findings showed that ovary mast cell numbers, corpus luteum angiogenesis, and vascular endothelial growth factor (VEGF) immunoreactivity in ovarian tissues increased with obesity and then significantly decreased with irisin administration. Also, it was determined that the increased serum oxytocin levels with obesity, increased markedly depending on irisin administration in obese female rats. Taken together, our findings revealed that irisin can well be considered as a potential therapeutic agent in the treatment of obesity by reducing mast cells and angiogenesis, and promoting oxytocin secretion.
Primjena irizina u pretilih štakora modificira broj mastocita u jajniku, ovarijsku angiogenezu i razine oksitocina Vet.
Keywords: irisin; obesity; mast cell; angiogenesis; oxytocin